Distribution and effects of the muscarinic receptor subtypes in the primary visual cortex - Groleau, Marianne; Kang, Jun Il; Huppé-Gourgues, Frédéric; Vaucher, Elvire (Frontiers in Synaptic Neuroscience, 2015)
Muscarinic cholinergic receptors modulate the activity and plasticity of the visual cortex. Muscarinic receptors are divided into 5 subtypes that are not homogeneously distributed throughout the cortical layers and cells types. This distribution results in complex action of the muscarinic receptors in the integration of visual stimuli. Selective activation of the different subtypes can either strengthen or weaken cortical connectivity (e.g., thalamocortical vs. corticocortical), i.e., it can influence the processing of certain stimuli over others. Moreover, muscarinic receptors differentially modulate some functional properties of neurons during experience-dependent activity and cognitive processes and they contribute to the fine-tuning of visual processing. These functions are involved in the mechanisms of attention, maturation and learning in the visual cortex. This minireview describes the anatomical-functional aspects of muscarinic modulation of the primary visual cortex’s microcircuitry.